Pengaruh Ukuran Perusahaan, Variabilitas Harga Pokok Penjualan, Likuiditas, dan Laba Sebelum Pajak Terhadap Pemilihan Metode Akuntansi Persediaan: - Teguh Erawati; Desi Ramadhani (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to examine the size of company, the variability of cost of goods sold, liquidity, and profit before tax on the selection of inventory accounting methods. To test the hypothesis used secondary data with a purposive sampling method. Data analysis technique used multiple linier regression analysis with company size, variability of the cost of inventory, liquidity, and profit before tax as variable (X) and the selection of inventory accounting methods as variable (Y). After data was analyzed, it was determined that partially the variability of cost of goods sold and liquidity had an effect on the selection of inventory accounting methods, while firm size and profit before tax had no effect on inventory accounting methods. Simultaneously the size of the company, the variability of cost of goods sold, liquidity and profit before tax together have a significant effect on the selection of inventory accounting methods. Keywords : firm size, variability of cost of goods sold, liquidity, profit before tax, selection of inventory accounting methods.